Pasynok V. G. Dialogism and dialogue of consciousness - Pasynok V. G. (Philological Treatises, 2020)
The theme of the article is based on the author’s desire to penetrate into the sphere of dialogical interaction of communicators which is connected with dialogism as a language and cultural phenomenon. Attention is given to functioning of cognitive factors in discourse, role of the linguistic personality in dialogical space.